Helicobacter pylori infection decreases gastric alcohol dehydrogenase activity and first-pass metabolism of ethanol in man - Simanowski, Ulrich; Egerer, Gerlinde; Oneta, Carl; Keil, Thomas; Parés, Xavier; Conradt, Christian; Arce, Luis; Waldherr, Rüdiger; Stickel, Felix; Russell, Robert M.; Aderjan, Rolf; Klee, Fritz; et al. (Digestion, 1998)
Background/Aims: Ethanol is metabolized by alcohol dehydrogenase in the human stomach. This metabolism contributes to the so-called first-pass metabolism of ethanol which is affected by gender, medication, and morphological alterations of the gastric mucosa. Recently, it has been shown that Helicobacter pylori is capable to oxidize ethanol to acetaldehyde in vitro. Since H. pylori also injures gastric mucosa, the present study examines the effect of this bacterium on gastric alcohol dehydrogenase activity and systemic availability of ethanol in vivo. Methods: Thirteen volunteers (7 men and 6 women, aged 18-52 years) with gastric H. pylori infection diagnosed by a positive CLO test and positive gastric histology received ethanol (0.225 g/kg) either orally or intravenously before and after H. pylori elimination to determine systemic availability of ethanol. In addition, gastric biopsy specimens were taken from all subjects before and after H. pylori elimination for histological assessment of mucosal alterations and determinations of gastric alcohol dehydrogenase activity and phenotype of the enzyme. Results: In the presence of H. pylori the first-pass metabolism of ethanol was found to be significantly reduced (625 ± 234 vs. 1,155 ± 114 mg/dl/min, p = 0.046). This reduction of first-pass metabolism of ethanol was associated with a significant decrease in alcohol dehydrogenase activity (4.8 ± 1.5 vs. 12.1 ± 2.3 nmol/mg protein × min, p < 0.05) and an increase in the severity of mucosal damage as determined by a histological score (p < 0.05). Conclusions: H. pylori infection leads to gastric mucosal injury which is associated with a decrease in gastric alcohol dehydrogenase activity and first-pass metabolism of ethanol. Ethanol metabolism by H. pylori does not play an important role in vivo. However, gastric morphology is one important factor determining systemic availability of ethanol in man.
Gesehen am 15.08.2023